2006
DOI: 10.1897/04-675r.1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cd, Cu, Ni, Pb, and Zn in a soil‐plant‐invertebrate food chain: A microcosm study

Abstract: The transfer of Cd, Cu, Ni, Pb, and Zn was evaluated in a soil-plant (lettuce, Lactuca sativa)-invertebrate (snail, Helix aspersa) food chain during a microcosm experiment. Two agricultural soils, polluted and unpolluted, were studied. Lettuce was cultivated for eight weeks before introduction of snails into the microcosms (M-snails). In a parallel experiment, snails were exposed to lettuce only (i.e., without soil) in simpler exposure devices called containers (C-snails). Snail exposure duration was eight wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
5
36
0
3
Order By: Relevance
“…Iron content in big apple snail (102 mg/100 g) and golden apple snail (48 mg/100 g) are far higher than the results presented in James (2006) for molluscs (7-26.6 mg/100 g) and CFCD (2002) for rice paddy field snail (19.7 mg/100 g). As snails ingest sludge from the surrounding paddy field (Scheifler et al, 2006), washing was a determining process in minimizing mineral content before the snails were analyzed. Thus there is a possibility that the high Table 6 Contents of calcium, zinc and iron in the analyzed fish, other aquatic animals and fermented fish a (mg/100 g samples).…”
Section: Ca Zn and Fe Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron content in big apple snail (102 mg/100 g) and golden apple snail (48 mg/100 g) are far higher than the results presented in James (2006) for molluscs (7-26.6 mg/100 g) and CFCD (2002) for rice paddy field snail (19.7 mg/100 g). As snails ingest sludge from the surrounding paddy field (Scheifler et al, 2006), washing was a determining process in minimizing mineral content before the snails were analyzed. Thus there is a possibility that the high Table 6 Contents of calcium, zinc and iron in the analyzed fish, other aquatic animals and fermented fish a (mg/100 g samples).…”
Section: Ca Zn and Fe Contentmentioning
confidence: 99%
“…Big apple snails contained the highest level (12 mg/100 g) and padek from Savannakhet market contain the lowest (0.35 mg/ 100 g). This may be due to the aforementioned ability of the snails to ingest sludge from the surrounding paddy field (Scheifler et al, 2006). The previously mentioned washing procedure in the laboratory may also influence the measurement of zinc content.…”
Section: Ca Zn and Fe Contentmentioning
confidence: 99%
“…Therefore, the Cu, Zn, and Cd assimilation in snails was mainly the result of transfer from amended lettuce leaves to snails. The contribution of soil to Pb assimilation in snails has been reported to be higher than 80 % (Scheifler et al 2006). Similarly, a recent study revealed that 89.9 % of assimilated Pb was transferred directly via the soil (Pauget 2012).…”
Section: Metal Inputs In Amended Soil and Their Bioavailability To Lementioning
confidence: 97%
“…The microcosms were placed on the ground over the natural vegetation and 10 mm mesh stainless steel netting was securely fitted over the top of the microcosm, avoiding the escape of the snails and predation. Therefore, the snails were able to feed on soil, litter and vegetation and were exposed via dermal, respiratory and digestive routes (Coeurdassier et al 2002;Fritsch et al 2008;Gimbert et al 2008b;Scheifler et al 2006). Microcosms were placed side by side (less than 1 meter apart) and animals of each group (C. aspersus ME or BE and C. nemoralis ME or BE) were randomly assigned to microcosms.…”
Section: Animalsmentioning
confidence: 99%
“…Snail faeces also clearly confirmed that the snails feed on the vegetation in the microcosms (personal observation). Snails can be exposed to pollutants via several routes: oral, dermal and respiratory (Coeurdassier et al 2002;Fritsch et al 2008;Gomot-de Vaufleury and Pihan 2000;Regoli et al 2006;Scheifler et al 2006). Concerning oral exposure, they can be exposed via trophic pathway, by eating soil, litter and vegetation.…”
Section: Effects On Snail Body Conditionmentioning
confidence: 99%